Enhancing Students’ Achievement in Descriptive Statistics by Emphasizing Statistical Reasoning - Tirangkoor, Sunhajutha; Chaiyasang, Supotch (ASEAN Journal of Education, 2023)
This study conducted classroom action research as a means to enhance students’ achievement in descriptive statistics by emphasizing statistical reasoning. Statistical reasoning is the method people reason with statistical ideas and make sense of statistical information. In this research, it was categorized into six groups which are reasoning about: (1) data collection, (2) frequency distributions, (3) measures of central tendency, (4) measures of positions, (5) measures of dispersions and (6) standard scores and normal distributions. The participants include 46 Grade 11 students in the first semester of academic year 2018 at a secondary school in Bangkok, Thailand. The topic in this study is descriptive statistics comprising: (1) statistics and data collection, (2) frequency distributions, (3) measures of central tendency, (4) measures of positions, (5) measures of dispersions and (6) standard scores and normal distributions. Instruments in this study consist of 8 lesson plans, achievement test, and reflection form. Teaching and learning lasted for 42 periods each at 50 minutes. This study had three cycles. Each cycle was composed of planning, acting, observing and reflecting. The results show that the effectiveness index is 0.60 which indicates that the students’ achievement was enhanced to the level required by the researcher (accepted effectiveness index must be greater than or equal 0.50). From reflections, the researcher found that using statistical reasoning increases students’ understanding and decreases students’ misconceptions. Statistical misconceptions of students include: misleading graphs, computation of combined means, using inappropriate central tendency, interpretation and properties of central tendency and dispersions.